(3CQHYhf MOjKkGs - (3YHO GdcQje Hf ghGRf Hf YHO Gdedc GHf WdMI GdfjSGHhQj GdbTjQj, CHh GdbGSe, Rjf GdESdGe,J (B465 (3g` s ((3CHh YHO Gddg eMeO Hf eNJGQ s)
(3ChdgG (B:s
(3CNHQfG GdCeGe GdRGgO GdYGde GdYGHO GdHjgbi CeG HYO aEf Gddg SHMGfg LYd eMeOkG fHjg UdhGJ Gddg Zdb NGJe CfHjGFg s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde ef CUGH eGdkG MdGdkG aca hLgg hhUd Hg QMeg hbVi Hg Ojfg hCbGe Hg Ydi LGQg dbi Gddg jhe GdbjGeI GdMOjK JeJ GdCQHYhf s
(3GdfSNI HgG MhGTs
(3HChdgG hBNQgG SeGYGJ ai GdbQfjf GdSGOS hGdSGHYs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B6s
Keywords: (3GdMOjK h GdeUWdMs